Differential T cell accumulation within intracranial and subcutaneous melanomas is associated with differences in intratumoral myeloid cells - Katarzyna Stasiak; Aaron D. Stevens; Ashley C. Bolte; Colleen T. Curley; Mirna Perusina Lanfranca; Robin S. Lindsay; Ukpong B. Eyo; John R. Lukens; Richard J. Price; Timothy N. J. Bullock; Victor H. Engelhard (Cancer Immunology, Immunotherapy)
Abstract Patients with metastatic brain melanomas (MBM) experience shorter-lasting survival than patients with extracranial metastases, and this is associated with a higher fraction of dysfunctional CD8 T cells. The goal of this study was to understand the underlying cause of T cell dysfunction in MBM. To accomplish this, we compared murine B16 melanomas implanted intracranially (IC) or subcutaneously (SC). CD8 T cell activation was not altered, but representation in IC tumors was lower. Transferred activated or naïve CD8 T cells accumulated in similar numbers in both tumors, suggesting that the vasculature does not differentially impair T cell presence. Surprisingly, we found no evidence for T cell activation in draining lymph nodes of SC or IC tumor-bearing mice, consistent with the fact that dendritic cells (DC) that had acquired tumor antigen showed an immature phenotype. Instead, T cell activation occurred within both tumors, where the majority of tumor antigen+ myeloid cells were found. While, the numbers of intratumoral DC were comparable, those in IC tumors acquired less tumor antigen, and were alternatively matured based on upregulation of MHCII without upregulation of CD86. Additionally, in IC tumors, the largest population of tumor antigen+ myeloid cells were microglia. However, their presence did not influence either antigen acquisition or the phenotype of other myeloid cell populations. Overall, our data suggest that diminished representation of CD8 T cells in IC tumors is a consequence of alternatively matured DC and/or microglia that induce distinctly activated T cells, which ultimately fail to continue to accumulate inside the tumor.